Revising the Pragmatics Profile Using a Modified Delphi Methodology to Meet the Assessment Needs of Current Speech-Language Therapists - Tan, Vanessa; Smidt, Andy; Herman, Gabi; Munro, Natalie; Summers, Susie (International journal of language & communication disorders, 2023)
Background: Non-standardized assessment tools are preferred when assessing communication of individuals with developmental disabilities. Currently, there are limited tools available for assessing this population. Informant report tools such as the Pragmatics Profile (PP) of Everyday Communication Skills are beneficial in gathering a representative view of an individual's communication. However, the PP is out of print and outdated, requiring revisions to meet contemporary assessment needs of speech-language therapists (SLTs). Aims: To seek consensus from an international panel regarding revising the Pragmatic Profile by (1) updating language and terminology, and (2) development of an online tool. Methods & Procedures: A total of 13 experienced SLTs and researchers in the disability field participated in a modified Delphi study including an initial online meeting followed by an anonymous four-round survey. Participants reviewed the relevance and wording of questions in the original preschool, school-age and adult versions to create a single combined version of the PP. In each Delphi round, the level of consensus was calculated and qualitative comments were analysed using thematic analysis. Outcomes & Results: A revised online version of the PP was created including 64 questions. Qualitative analysis illuminated key concepts in the creation of a revised form including the need for plain and age-neutral language, which is inclusive of all communication modalities and physical impairments, and identifies behaviours that have the potential to be communicative acts. Using conditional logic, users are navigated to the appropriate questions based on the intentionality level of the individual rather than their age. Conclusions & Implications: This study resulted in the revision of a valued assessment tool appropriate for current disability service provision that identifies communication along the continuum of intentionality rather than age.